Flipped Classroom Approach in Developing English Language Learning Curriculum in the Digital Era - Rahmah, Nabilah Julia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Flipped Classroom is a learning model that reverses the habits of traditional learning methods, usually learning activities carried out in class such as understanding the material, then done at home, while assignments or homework that is usually done at home is done in class. This approach encourages students to be more independent and responsible for their own learning process, with the teacher acting as a facilitator. Since its implementation by Bergmann and Sams in 2007, the flipped classroom has become an increasingly popular pedagogical strategy. In the context of curriculum development and educational transformation in the digital era, the flipped classroom can be integrated into the current student-based system. (student-centered learning), collaboration and digital literacy, especially in English language teaching. Integrating a flipped classroom approach using digital media can support curriculum objectives by offering flexibility, effectiveness and innovation in learning. This approach makes it easier for students to learn and understand materials through digital media at home, and focus on active discussion and practice in class. Curriculum in the digital era adapts to prepare students to have critical, collaborative and creative thinking skills. With information and communication technology, utilizing digital media such as learning videos, interactive modules, and online discussion platforms into the flipped classroom approach will allow students to access materials and information more flexibly and in-depth.